2002
DOI: 10.1007/s00445-002-0248-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-period events and tremor at Popocatepetl volcano (1994–2000) and their broadband characteristics

Abstract: Following an initial phreatic eruption on 21 December 1994, activity at Popocatepetl has been dominated by fumarolic emissions interspersed with more energetic emissions of ashes and gases. A phase of repetitive dome-building and dome-destroying episodes began in March 1996 and is still ongoing at present. We describe the long-period (LP) seismicity accompanying eruptive activity at Popocatepetl from December 1994 through May 2000, using data from a three-component broadband seismometer located 5 km from the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(25 citation statements)
references
References 40 publications
(38 reference statements)
2
22
1
Order By: Relevance
“…In addition, the source location of Colima Type A events furnishes very shallow solutions in the crater area, which further indicates a close relationship with the observed explosive activity. This is in agreement with the observations of several authors (Uhira and Takeo 1994;Hagerty et al 2000;Arciniega-Ceballos et al 2003) who found that the seismicity related to the volcano's explosive activity occurs at shallow depths (0-2 km).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, the source location of Colima Type A events furnishes very shallow solutions in the crater area, which further indicates a close relationship with the observed explosive activity. This is in agreement with the observations of several authors (Uhira and Takeo 1994;Hagerty et al 2000;Arciniega-Ceballos et al 2003) who found that the seismicity related to the volcano's explosive activity occurs at shallow depths (0-2 km).…”
Section: Discussionsupporting
confidence: 93%
“…Among them, long period (LP) events, characterized by emergent onset, absence of clear shear wave (S) arrivals and typical spectral content in the range 0.2-2 s, are recognized as important indicators of the state of the volcano, being strictly related to the dynamics and to the physical processes acting at the source (Chouet 1996). LP seismicity has often been observed concomitant with volcanic explosions (Uhira and Takeo 1994;Hagerty et al 2000;Arciniega-Ceballos et al 2003), though in other cases its occurrence is not directly related to any visible activity (Kumagai et al 2002;Petersen et al 2006). LP waveforms and their spectral content can be explained in terms of interaction between the Editorial responsibility: M. Ripepe S. Petrosino (*) : P. Cusano : M. La Rocca : D. Galluzzo : E. Del Pezzo Istituto Nazionale di Geofisica e Vulcanologia, Sezione di Napoli-Osservatorio Vesuviano, Via Diocleziano 328, 80124 Naples, Italy e-mail: simona.petrosino@ov.ingv.it fluid flows and the plumbing system, and depend on the fluid density, the type of Moment Tensor acting at the source, and the geometry of the cracks or conduits (Crosson and Bame 1985;Chouet 1986Chouet , 1988Nishimura 1998).…”
Section: Introductionmentioning
confidence: 99%
“…During those phases, SO 2 degassing has increased progressively and varied according to the intensity of the observed surface activity. This behaviour is similar to that observed until 2005 and comparable to Popocatépetl until 2000, when activity was also more-or-less continuous (Delgado-Granados et al, 2001;Arciniega-Ceballos et al, 2003). These long periods of activity display a low slope in the relation between total cumulative SO 2 emission and the duration of the phase (Fig.…”
Section: Tablesupporting
confidence: 81%
“…Once the vent is open, the activity would change to more Strombolian-like style or continue with lower energy Vulcanian explosions. Short activity phases have been observed in other andesitic volcanoes, like Ruapehu and recently Popocatépetl, but the periods of quiescence in those cases seem longer (months to years) (Nakagawa et al, 1999;Arciniega-Ceballos et al, 2003). According to the relatively small size of the recent eruptions (VEI = 1; Bernard et al, 2013), it seems that the critical volume of magma required to trigger an eruption can be built up faster.…”
Section: Tablementioning
confidence: 92%
“…In late March 1996, a lava dome was first observed in the crater. This dome was partially destroyed on 30 April 1996, when a large eruption initiated a long phase of repetitive dome‐building and dome‐destroying episodes that continued through March 1999 [ Arciniega‐Ceballos et al , 2003]. Activity remained limited to emissions of ash and gas and intermittent lava effusions during the next twenty months, following which explosive activity resumed with a large dome‐destroying event on 17 December 2000.…”
Section: Introductionmentioning
confidence: 99%